Direct profiling of the phospholipid composition of adult Caenorhabditis elegans using whole-body imaging mass spectrometry - Hameed, Saira (Anal Bioanal Chem, 2015)
A protocol for the direct analysis of the phospholipid composition in the whole body of adult soil nematode, Caenorhabditis elegans (C. elegans), was developed, which combined freeze-cracking of the exoskeletal cuticle and matrix-assisted laser desorption/ionization-imaging mass spectrometry (MALDI-IMS). Biomolecules in the m/z range from 700 to 900 were more effectively detected in the freeze-cracked than from simple frozen adult nematode bodies. Different distribution of biomolecules was observed in a nematode body when the matrix was applied with a sublimation deposition method. The whole-body IMS technique was applied on genetically deficient mutant C. elegans to combine whole-body lipidomics and genetics, by comparing the fatty acid compositions, especially of the phosphatidylcholine (PC) species, between the wild-type and fat-1 mutants, which lack the gene encoding an n-3 fatty acid desaturase. A significant reduction of PC(20:5/20:5) and PC(20:4/20:5) and a marked increase of PC(20:4/20:4), PC(20:3/20:4), and PC(20:3/20:3) were detected in the fat-1 mutants in positive ion mode. In addition, phospholipid compositions other than PCs were analyzed in negative ion mode. A loss of a possible phosphatidylinositol (PI) with 18:0/20:5 and a compensative accumulation of putative PI(18:0/20:4) were detected in the fat-1 mutants. In conclusion, the whole-body MALDI-IMS technique is useful for the profiling of multiple biomolecules in C. elegans in both intra- and inter-individual levels. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00216-015-8932-7) contains supplementary material, which is available to authorized users.